2014
DOI: 10.1080/10618600.2013.842489
|View full text |Cite
|
Sign up to set email alerts
|

Variable Selection in General Frailty Models Using Penalized H-Likelihood

Abstract: Il Do HA, Jianxin PAN, Seungyoung OH, and Youngjo LEE Variable selection methods using a penalized likelihood have been widely studied in various statistical models. However, in semiparametric frailty models, these methods have been relatively less studied because the marginal likelihood function involves analytically intractable integrals, particularly when modeling multicomponent or correlated frailties. In this article, we propose a simple but unified procedure via a penalized h-likelihood (HL) for variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(101 citation statements)
references
References 40 publications
5
96
0
Order By: Relevance
“…It is well known that shrinkage estimations would be preferred for prediction (Efron and Morris, 1975;. Ha et al (2014) have showed via simulations that the HL has higher probability of choosing the true model than the LASSO and SCAD methods without losing prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is well known that shrinkage estimations would be preferred for prediction (Efron and Morris, 1975;. Ha et al (2014) have showed via simulations that the HL has higher probability of choosing the true model than the LASSO and SCAD methods without losing prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Here they considered three penalty functions (LASSO, SCAD and HL). In this paper we propose a simple variable-selection procedure in Poisson HGLMs (Lee and Nelder, 1996) using Ha et al's (2014) method. Here, the Poisson HGLMs with random effects are very useful for analyzing correlated count data.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations